2016
DOI: 10.1108/jm2-12-2013-0067
|View full text |Cite
|
Sign up to set email alerts
|

Development of fuzzy two-stage DEA model for competitive advantage based on RBV and strategic agility as a dynamic capability

Abstract: Purpose – This paper aims to develop a framework for competitive advantage by systematic quantitative methodology based on resource-based view and dynamic capability theory. Strategic agility was used as a dynamic capability. Design/methodology/approach – Data were collected from a survey aimed at manufacturing companies from five manufacturing industry in Semnan, Iran. A total of 102 questionnaires were received from 13 companies using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 42 publications
1
25
0
1
Order By: Relevance
“…In observing the results of the measurement model and the structural model of Tables 6 and 7, we concluded that we developed formative constructs: IC, IIO, IS and INR, interesting to be evaluated by new studies in this sector. This contributes to encourage discussions about resources that are firm and to establish the relationship between these resources as strategic agility, competitive advantage and which could be studied in the light of dynamic capabilities theory (Hemmati et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In observing the results of the measurement model and the structural model of Tables 6 and 7, we concluded that we developed formative constructs: IC, IIO, IS and INR, interesting to be evaluated by new studies in this sector. This contributes to encourage discussions about resources that are firm and to establish the relationship between these resources as strategic agility, competitive advantage and which could be studied in the light of dynamic capabilities theory (Hemmati et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…These authors present an alternative to RBV that they called the practice-based view (PBV) for operations management in explaining the full range of company performance based on transferable practices. Our study considers these alternatives seeking to establish the relationship between the company's resources, strategic agility, competitive advantage (Hemmati et al., 2016), including the vision of an efficient operation. Kellermanns et al., (2016), say that RBV aims to help researchers understand why some companies enjoy a competitive advantage in order to outperform other firms.…”
Section: Introductionmentioning
confidence: 99%
“…Literature has regarded strategic agility as a higher-order dynamic capability. Tikkanen (2014) observed that dynamic capabilities do influence parts of strategic agility in a dynamic industry; Teece, Peteraf, and Leih (2016) asserted that strong dynamic capabilities are necessary for fostering the organizational agility necessary to address deep environmental uncertainty; and Hemmati, Feiz, Jalilvand, and Kholghi (2016) regarded strategic agility as a dynamic capability in developing a framework for competitive advantage by systematic quantitative methodology. Their study confirmed the intermediate role of strategic agility as a dynamic capability between resources and competitive advantage.…”
Section: Discussionmentioning
confidence: 99%
“…2 In the study of strategic agility of manufacturing companies, hemmati et al Used the method of questionnaire survey and used fuzzy Two-stage DEA model to analyze the collected questionnaire data. 3 The results show that there is a close internal relationship among enterprise resources, strategic agility and competitive advantage, and this relationship makes the company's return to scale close to 1 al.2016. used DEA model to study the coverage efficiency of rural health centers in southern Greece.…”
Section: Introductionmentioning
confidence: 93%